Ahead of the Curve: Tracking Progress in Novice Microsurgeons - Brosious, John P.; Kleban, Shawna R.; Goldman, Joshua J.; Mohsin, Adnan G.; Williams, Shelly J.; Wang, Wei Z.; Menezes, John M.; Baynosa, Richard C. (Journal of Reconstructive Microsurgery, 2019)
Background The purpose of this study was to evaluate learning curves for an existing microsurgical training model. We compared efficiency and amount of training needed to achieve proficiency between novice microsurgeons without operative experience versus those who had completed a surgical internship.Methods Ten novice microsurgeons anastomosed a silastic tube model. Time to perform each anastomosis, luminal diameter, and number of errors were recorded.Results First year residents improved up to a brief plateau at 10 repetitions, followed by continued improvement. Second year residents improved up to a plateau at 10 repetitions with no further improvement thereafter. There was no significant difference in luminal area or errors between groups.Conclusion Residents with no operative experience can benefit from early exposure to microsurgical training. These interns continue to improve with additional repetitions while second year residents achieve proficiency with fewer repetitions.
Keywords: microsurgical skills; surgical simulation; microsurgical training